Synthesis and Biological Evaluation of Some 1, 8-Naphthalimide-Acridinyl Hybrids. (5th August 2020) - Chen, Rui; Yuan, Caiying; Jaiswal, Yogini; Huo, Lini; Li, Dianpeng; Williams, Leonard; Zhong, Jing; Liang, Yan
Abstract : In the present study, the synthesis of three 1, 8-naphthalimide-acridinyl hybrids (2a, 2b, and 5b ) using N-amido-1, 8-naphthalimides (1 and 4 ) and acridinyl isothiocyanates is reported. The newly synthesized hybrids were evaluated for their anticancer activity in six human cancer cell lines (HL-60, MT-4, HepG2, HeLa, SK-OV-3, and MCF-7). Their inhibition activity against DNA-topoisomerase I (Topo I) and Electrophorus electricus acetylcholinesterase (AChE) was also studied. The results indicate that 2b displayed good cytotoxicity for MT-4, HepG2, HeLa, and SK-OV-3 with the IC50 values of 14.66 ± 0.31, 27.32 ± 2.67, 17.51 ± 0.34, and 32.26 ± 1.74 μ M, respectively. All compounds, especially 2b, exhibited obvious bands corresponding to DNA fragments at 0.5 mM concentration, further confirming the pharmacological mechanism related to the Topo I inhibitory activities. In addition, compound 2a exhibited higher inhibition activity against AChE than 2b and 5b, with IC50 values of 0.32 ± 0.04 mM, and the acridinyl ring may contribute to the activity of 2a .